Improved overall survival with checkpoint inhibition and allogeneic transplantation in relapsed Hodgkin lymphoma - Nadeem Tabbara; Marianna Zahurak; Cole H. Sterling; Iris Margalit Trutzer; Jaroslaw Jedrych; Lode J. Swinnen; Ephraim J. Fuchs; Javier Bolaños-Meade; Nina Wagner-Johnston; Richard J. Jones; Richard F. Ambinder; Ravi Varadhan; et al. (Blood Advances)
Abstract: Patients with relapsed classic Hodgkin lymphomas (cHLs) receive salvage therapy with immune checkpoint inhibitors (ICIs) or chemotherapy (no-ICI). Patients responding to therapy often undergo consolidation with allogeneic blood or marrow transplantation (alloBMT). We previously reported that relapsed patients with cHL treated with ICI followed by alloBMT experienced improved 3-year progression-free survival (PFS) compared with patients treated with salvage chemotherapy without ICI followed by alloBMT. In this retrospective analysis, we report the 5-year overall survival (OS), PFS, and graft-versus-host disease (GVHD) incidence in patients with cHL treated with ICI before alloBMT with post-transplantation cyclophosphamide GVHD prophylaxis. Among the 147 relapsed/refractory patients with cHL, 71 (48.3%) received ICIs and 76 (51.7%) received chemotherapy without ICIs (no-ICI) before alloBMT. We observed an improved 5-year estimated OS of 91% (ICI) vs 66% (no-ICI; hazard ratio [HR], 0.39; 95% confidence interval [CI], 0.16-0.98; P = .046) and a 5-year estimated PFS of 84% (ICI) vs 53% (no-ICI; HR, 0.4; 95% CI, 0.2-0.81; P = .011). The 12-month cumulative incidence of grade 3 to 4 GVHD was 20% (ICI) and 7% (no-ICI; subdistribution hazard ratio (SDHR), 3.16; 95% CI, 1.13-8.81; P = .03). More frequent grade 3 to 4 acute GVHD was likely due to the higher incidence of grade 3 to 4 acute GVHD in the subset of patients with pretransplant exposure to ICI and shortened duration (60 days) of immunosuppression vs patients with long immunosuppression (day 180). These data suggest that patients with cHL treated with ICI and alloBMT experience improved OS, and the GVHD risk can be mitigated by immunosuppression until day 180.